THE EFFECT OF USING ELECTRONIC STANDS IN TEACHING ROBOTICS - Shyndaliyev, Н.; Ramankulov, А.; Zulpykhar, Ж.; Kulmagambetova, Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
As part of a joint experiment of Aktobe Regional University and Eurasian National University, a study was conducted to assess the effectiveness of using electronic stands in robotics training. The experiment involved 70 students, divided into control and experimental groups. A 25-question test was used to assess prior knowledge. According to the results of the experiment, which lasted one semester, a statistically significant improvement in the level of knowledge in the experimental group was revealed, with a (p)-value of 0.0101. The survey showed that the majority of students positively assessed the new approach to learning. The results of the study confirm the potential of integrating electronic stands into the educational process and their impact on improving the quality of robotics training. This discovery is important for the further development of the field of robotics and education in general. An innovative approach can become the basis for the development of new teaching methods and the improvement of educational technologies that contribute to the formation of the necessary skills in the field of high technology.